The effect of watching funny and unfunny videos on post-surgical pain levels - (:unkn) unknown (ELSEVIER SCI LTD, 2017)
Objective: The aim of this study was to describe pain intensity before and after watching funny and unfunny videos on post-surgical pain levels. Methods: Ninety patients were divided into three groups. Group A watched funny videos, Group B watched unfunny videos, Group C did not watch any videos. Pain assessment of the patients was carried out before (first), immediately after (second), and 30 min after (third) watching videos. Results: The first pain scoremean in Group A was 40.83 +/- 22.62, in Group B was 37.46 +/- 24.31, in Group C was 48.86 +/- 24.06. The second pain scoremean in Group A was 32.93 +/- 20.28, in Group B was 29.76 +/- 20.26, in Group C was 48.96 +/- 24.11. The third pain scoremean in Group A was 37.43 +/- 23.07, in Group B was 36.80 +/- 22.67, in Group C was 5230 +/- 23.97. Conclusion: Watching funny or unfunny videos reduces the post-surgical pain level. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Pain; Funny-unfunny videos; Orthopedic patients; Nursing; Watching video; INFLUENCE HEALTH; HUMOR; LAUGHTER; DISTRACTION; MOOD